PERAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH DIPENGARUHI OLEH JUMLAH PENDUDUK KABUPATEN BEKASI : Kata kunci: Efektivitas, kontribusi, pajak restoran, jumlah penduduk, pendapatan asli daerah. - adibah yahya (Accounthink, 2020)
Regional tax income collected by local governments is Regional Original Income (PAD). Restaurant tax is part of local taxes, the research objective is to analyze the effectiveness and contribution of restaurant taxes to local revenue and its effects which are moderated by the number of residents. The ratio of effectiveness and contribution is used in this study by looking at the target and realization of restaurant taxes on local revenue. Revenue from restaurant tax always increases every year in Bekasi Regency, which is a phenomenon that is used as a source of research. This research uses descriptive analysis method, hypothesis testing is done partially and moderately. The study population is a sample of research with 2013-2017 research data. The research results show that there is a partial effect of the effectiveness and contribution of restaurant taxes on local revenue, while the population has no effect on local revenue. The moderation test shows that the total population is not a moderating variable between the effectiveness and contribution of restaurant taxes to local revenue, this shows that the population cannot strengthen the effect of the effectiveness and contribution of local taxes to local revenue. Keywords: Effectiveness, contribution, restaurant tax, total population, locally-generated revenues